2018
DOI: 10.1093/jamia/ocy112
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and unintended consequences of hard-stop alerts in electronic health record systems: a systematic review

Abstract: Hard stops can be effective and powerful tools in the CDS armamentarium, but they must be implemented judiciously with continuous user feedback informing rapid, iterative design. Investigators must report on associated health outcomes and unintended consequences when implementing IT solutions to clinical problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 55 publications
0
71
0
Order By: Relevance
“…Using the techniques of improving relevance, soliciting feedback, customization, measurement of outcomes and metrics, and iteration, the effects of CDS on burnout can be ameliorated. [20,24,97] -Role tailoring of alerts [21,82] -Tiering of alerts [20,80] -Iterative design [25] Harmful -Interruptive or hard stop alerts [21,25,80] -Lack of "right information" [18] -Lack of relevance [80,97,108] -Lack of integration [78]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the techniques of improving relevance, soliciting feedback, customization, measurement of outcomes and metrics, and iteration, the effects of CDS on burnout can be ameliorated. [20,24,97] -Role tailoring of alerts [21,82] -Tiering of alerts [20,80] -Iterative design [25] Harmful -Interruptive or hard stop alerts [21,25,80] -Lack of "right information" [18] -Lack of relevance [80,97,108] -Lack of integration [78]…”
Section: Resultsmentioning
confidence: 99%
“…In evaluating the user experience, the authors found that CDS for which the end users were involved in design and iteration were the most acceptable. Hard stops for documentation purposes were poorly received [25].…”
Section: The Big Picture -Review Articlesmentioning
confidence: 99%
“…Restriction of choice [39] The removal of an order option ultimately resulted in fewer laboratory tests and reduced healthcare expenditure in all studies. [14,28,31] Finally, we identi ed two different types of implemented hard-stops: [40] an interruptive alert [30] and a restrictive hard-stop [14]. An interruptive alert requires a clicking response from the physician before being able to move forward.…”
Section: Resultsmentioning
confidence: 99%
“…First, as our goal was to understand how prescribers acting of their own free will responded to different interventions, we excluded "hard stops," which impose heavy time penalties to override, and which therefore materially restrict the prescriber's range of action. Readers interested in an analysis of hard stops should refer to a 2018 systematic review by Powers et al 6 Second, we excluded articles that did not describe the interactive design in enough detail to produce a description. Third, we excluded articles in which researchers made global changes to an alerting system, but only reported acceptance rates for those alerts intended to convey the most urgency, for certain drug categories, or for a selected subset of users exposed to the alert; some of these authors may have chosen to report only the most palatable results.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…For example, in some instances, "hard stops" have prevented patients from receiving potentially life-saving treatment in time. 6 The information technology infrastructures that organizations must install to integrate CDS into the medicationordering process-often accompanied by changes in workflow and communication patterns-can disrupt work during "roll-out," as well as in long-term use. 7 These disruptions can increase instances of ADEs, which can, in turn, increase patient mortality.…”
Section: Introductionmentioning
confidence: 99%